Evaluating the efficacy of oxytocin for pain management: An updated systematic review and meta-analysis of randomized clinical trials and observational studies - Anastasia A. Mekhael; Jennifer E. Bent; Jonathan M. Fawcett; Tavis S. Campbell; Aldo Aguirre-Camacho; Alison Farrell; Joshua A. Rash (Taylor & Francis Group, 2023)
ABSTRACTBackground There is a need for novel analgesics with favorable risk to benefit profiles. Oxytocin has recently gained attention for its potential analgesic properties.Aim The aim of this study was to perform an updated systematic review and meta-analysis evaluating the effect of oxytocin for pain management.Method Ovid MEDLINE, Embase, PsycINFO, CINAHL, and Clinicaltrials.gov were searched for articles reporting on associations between oxytocin and chronic pain management from January 2012 to February 2022. Studies published before 2012 that were identified in our previous systematic review were also eligible. Risk of bias of included studies was assessed. Synthesis of results was performed using meta-analysis and narrative synthesis.Results Searches returned 2087 unique citations. In total, 14 articles were included that reported on 1504 people living with pain. Results from meta-analysis and narrative review were mixed. Meta-analysis of three studies indicated that exogenous oxytocin administration did not result in a significant reduction in pain intensity relative to placebo (N = 3; n = 95; g = 0.31; 95% confidence interval [CI] −0.10, 0.73). Narrative review provided encouraging evidence that exogenous oxytocin administration reduced pain sensitivity among individuals with back pain, abdominal pain, and migraines. Results suggested that individual difference factors (e.g., sex and chronic pain condition) may influence oxytocin-induced nociception, but the heterogeneity and limited number of studies identified precluded further investigation.Discussion There is equipoise for the benefit of oxytocin for pain management. Future studies are imperative and should undertake more precise exploration of potential confounds and mechanisms of analgesic action to clarify inconsistency in the literature.